A dynamic model as a tool for design and optimization of propulsion systems of transport means - Peruń, Grzegorz (Zielona Góra: Uniwersytet Zielonogórski)
Designing power transmission systems is a complex and often time-consuming problem. In this task, various computational tools make it possible to speed up the process and verify a great many different solutions before the final one is developed. It is widely possible today to conduct computer simulations of the operation of various devices before the first physical prototype is built.
Keywords: dynamic models; gear; power transmission system; optimization; diagnostics